Comparative investigation of the effect of corrosion on the mechanical properties of different parts of thin-walled steel. (January 2020) - Zhang, Zongxing; Xu, Shanhua; Li, Rou
Abstract: To comparatively investigate the effect of corrosion on the mechanical properties of different parts of C-shaped thin-walled steel, the flat and corner parts of C-shaped steel purlin, with a service life of 9 years in an industrial environment, were processed into the tested specimens. The effect of corrosion on the cold-formed effect of C-shaped thin-walled steel was investigated by fracture morphology and stress-strain curves. Thus, three methods for calculating the yield strength of cold-formed steel with corrosion damage were also proposed. Finally, based on reverse reconstruction technology, ABAQUS software was used to analyse the effect of corrosion surface morphology on the stress distribution and for the same specimens with different thicknesses. The results showed that different fracture modes and characteristics occurred in both the flat and corner parts after corrosion, which can be attributed to the corrosion surface and thickness reduction. With an increasing degree of corrosion, the strength of the corner parts obviously decreased more than the strength of the flat parts. When the corrosion ratio was 36%, the yield ratio of the corner parts was as high as 0.99, and the elongation was only 2.8%. The corrosion aggravated the cold-formed effect on the strength and the ductility of cold-formed materials. In addition, the corrosion surface will lead to the unbalanced development of surface stress, resulting in the diversification of fracture paths and locations. Especially when the corrosion surface was more uneven with depth, the stress at the maximum corrosion depth was always greater than the stress at other locations. The effect of the corrosion surface on the mechanical properties was related to the residual thickness of the specimens and increased with thinner residual thickness. Highlights: The effect of corrosion on cold-formed effect of thin-walled steel was investigated The method for calculating yield strength of corroded cold-formed steel was proposed. The effect of corrosion surface morphology on the stress distribution and fracture paths was investigated.